1991
DOI: 10.1088/0953-4075/24/7/022
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of double capture in Ne8++He, H2, by electron spectroscopy at 80 keV. I. Theoretical considerations

Abstract: Positions, autoionization and radiative probabilities of Ne6*(ls23131'), Ne"(ls'3141')and some Neei(lsz4141') states have been calculated with the AUTOLSJ method and compared with other recent theoretical data. Thhese results will he comparzd with our experimental electron spectra in a companion paper.The theoretical basis of the electron spectra analysis discussed in lhe companion paper is also established. Various kinds of perturbations of the electron lineshapes and angular distributions (autoionization fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
4
26
0
Order By: Relevance
“…The undetected ion beam was collected at the Attached to the target gas cell is a glass ion gauge which allows the target pressure to be monitored before and after each run. Experimental results for the system Ne ++He have been obtained (Boudjetna et al [4]) at the collisional velocity of 0.40 a.u. They observed the projectile Auger electrons emitted at laboratory angles of 10', 90', and 160.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The undetected ion beam was collected at the Attached to the target gas cell is a glass ion gauge which allows the target pressure to be monitored before and after each run. Experimental results for the system Ne ++He have been obtained (Boudjetna et al [4]) at the collisional velocity of 0.40 a.u. They observed the projectile Auger electrons emitted at laboratory angles of 10', 90', and 160.…”
Section: Methodsmentioning
confidence: 99%
“…[2), Moretto-Cappelle et al [3], Boudjema et al. [4], Rocin, Barat, and Larent [5], and Barat and Rocin [6], and references therein). These previous experiments have involved projectiles with collisional velocities well below one atomic unit of velocity.…”
Section: Introductionmentioning
confidence: 99%
“…We use a scaling factor of 0.85. Our results obtained by the MZ and Cowan codes are compared in table 2 with results obtained by Vaeck and Hansen (1989), Bachau et al (1990), Chen and Lin (1989) and Boudjema et al (1991a). These data are listed in table 2 (a, b, c, d, e, f, respectively).…”
Section: Theoretical Methodsmentioning
confidence: 78%
“…Experimental data are given in the column Exp. a1, b1, this work; a2, b2, Bachau et al (1990); a3, b3, Boudjema et al (1991a).…”
Section: Auger Widths (E)mentioning
confidence: 86%
“…Electron spectroscopy has been used most often to investigate the collision dynamics and the decay of doubly excited states populated in two-electron transfer processes. An analysis of this collision system has been done by Boudjema et al,͓2, where also references to previous work can be found. Photon spectroscopy is not often used, since the doubly excited states populated in the double electron transfer processes mainly stabilize by Auger decay.…”
Section: Introductionmentioning
confidence: 99%